PENGARUH MODERASI STRATEGI INOVASI KINERJA PADA PELAYANAN PUSKESMAS DI PALANGKA RAYA - Peridawaty; Noorjaya Nahan; Rita Yuanita Toendan (Media Bina Ilmiah, 2022)
This study aims to improve organizational performance with servant leadership style and transformational leadership. The services provided are a benchmark for the success of organizational performance which has an impact on improving the perceived service quality. The research was conducted using SEM PLS on 150 user employees in the four public health centers of the city of Palangka Raya. The results showed that servant leadership and performance innovation strategy moderation were not significant on organizational performance. The variables of transformation leadership and innovation strategy moderation performance are significant on organizational performance. The implications of the results in improving organizational performance based on health services require transformational leadership and performance innovation strategies.